Comparison of Paper Cases Versus Video Cases for Case-Based Learning in Physiotherapy Students: A Cross Over Study - Winter, Sara; Craig, Victoria (International Journal of Practice-based Learning in Health and Social Care, 2025)
Case-based learning (CBL) is a pedagogical method linking theory with practice, typically using developed or real-life patient cases. The aim of this study was to compare the effectiveness of paper versus video cases for CBL in physiotherapy students on performance of a clinical reasoning exercise and student’s evaluations of each method. A cross-over design study was used. Twenty-nine first year physiotherapy students were allocated to two groups. Two case scenarios were used with group one assigned the paper case for case one, group two the video case, and then the groups crossed-over CBL formats. Paired t tests were used to compare the clinical reasoning exercise score between the paper and video cases, and for quantitative measures of student’s evaluations of each method. Thematic analyses were performed to assess qualitative measures of student’s perceptions of the CBL formats. There were no significant differences in total score of the clinical reasoning exercise between the two formats (p>0.05), and inconsistent findings in the individual questions. Quantitatively and qualitatively the student’s evaluated that the video case format was better for authenticity, and the paper cases provided more accessible and comprehensive information. This study found that paper and video cases are both beneficial in different respects for the learning and development of the assessment and clinical reasoning process in first year physiotherapy students. Teachers should use both methods for CBL but consider the strengths and weaknesses of both methods when choosing which format to use.